Urgensi Penguatan Pengawasan Eksternal Yayasan Sebagai Bentuk Preventif Atas Penyalahgunaan Dana Yayasan (Studi Kasus Yayasan Aksi Cepat Tanggap) - Tiara Alfarissa; Muhammad Fauzan; Keren Shallom Jeremiah; Nicholas Christiansen; Lisa Angelie Putrie; Zahra Calista Herjendro; Mulyadi M (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Foundations are legal entities whose assets are separated to meet their goals and operate in three areas, namely social, religious and humanitarian. For example, with the goal of a foundation to pursue profit, it is precisely in this case that it also has great potential to commit or be open to committing such fraud. One of them is the Aksi Cepat Tanggap Foundation. The fact is that there are approximately 2 (two) trillion in funds managed by the Foundation and 103 (one hundred and three) billion found in the results of the investigation. The discussion that will become the basis and limitations of this research is explained by the formulation of the problem, namely, How are community fundraising foundations regulated in Indonesia?, and What are the forms of external supervision for fundraising foundations as a form of reducing the misuse of foundation funds This research was conducted using a normative juridical method with a Legislative Approach, Case Comparison, and Prescriptive Research. The results of the research show that the foundation law regarding the Indonesian supervisory board is still weak, because the provisions of the law do not explicitly state that people must come from outside or within the foundation. This can lead to legal smuggling and conflict of interest if there is no regulation on this matter. Oversight from the Attorney General is also passive. This passive supervision causes ineffectiveness in supervising all foundations in Indonesia, especially foundations engaged in public fundraising.